The Contribution of Speed and Leg Muscle Strength to Passing Performance in University Football Students - Mardepi Saputra; Riand Resmana; Yogi Arnaldo; Ardo Okilanda; Ozha Wahyu Pra Adha (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
Background and Study. Passing is a fundamental skill in football that requires not only technical proficiency but also adequate physical conditioning. This study aimed to examine the contribution of speed and leg muscle strength to passing performance among university students. Methods. A quantitative correlational design with multiple regression analysis was employed in this study. The participants were 100 male students from the Physical Education, Sport, and Recreation program. Data were collected using a 30-m sprint test to measure speed, a standing broad jump test to assess leg muscle strength, and a short passing test to evaluate passing performance. The data were analyzed using correlation and multiple regression techniques. Results. The results showed that speed was significantly correlated with passing performance (r = 0.62, p < 0.05), as was leg muscle strength (r = 0.58, p < 0.05). Both variables had significant partial and simultaneous effects on passing performance, accounting for 42% of the total variance. Discussion and Conlusions. These findings indicate that improving speed and leg muscle strength plays an important role in enhancing passing quality and effectiveness; therefore, these components should be prioritized in university football training programs.